Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

Regulation of venom composition by the Australian funnel-web spider Hadronyche infensa is achieved via compartmentalised toxin production and venom metering - David Morgenstern; Brett Hamilton; Darren Korbie; Karl R. Clauser; Brian J. Haas; Greg Bowlay; Kjetil L. Voje; Alun Jones; Deon J. Venter; Glenn F. King; Eivind A.B. Undheim (Toxicon, 2026)

Embracing Holistic Formulation Strategies to Maximise Positive Outcomes in Aquaculture Nutrition - Artur N. Rombenso; Brett D. Glencross; Kyla Zatti; Helen Ann Hamilton; Luiz H. David; Ha H. Truong; Cedric J. Simon (Reviews in Aquaculture, 2026)

Growth of a passive lava lake during the 2020–2021 eruption of Kīlauea volcano, Hawaii - Brett B. Carr; Matthew R. Patrick; Hannah R. Dietterich; Michael H. Zoeller; Carolyn E. Parcheta; Drew T. Downs; Patricia A. Nadeau; Christopher W. Hamilton (Bulletin of Volcanology, 2025)

A novel approach for quantifying elongated airborne mineral particles (EMPs) using an automated scanning electron microscope (SEM) - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Ayrton Hamilton; Wenxia (Wendy) Fan; Shuoyu Chen; Nick Talbot; Shanon Lim; Jed Januch; Martin Brook; Brett Wells; David E. Williams; et al. (Atmospheric Environment, 2025)

Venoms for all occasions: The functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function - Lauren M. Ashwood; Eivind A. B. Undheim; Bruno Madio; Brett R. Hamilton; Marymegan Daly; David A. Hurwood; Glenn F. King; Peter J. Prentis (Molecular Ecology, 2022)
The phylum Cnidaria is the oldest extant venomous group and is defined by the presence of nematocysts, specialized organelles responsible for venom production and delivery. Although toxin peptides and the cells housing nematocysts are distributed across the entire animal, nematocyte and venom profiles have been shown to differ across morphological structures in actiniarians. In this study, we explore the relationship between patterns of toxin expression and the ecological roles of discrete anatomical structures in Telmatactis stephensoni . Specifically, using a combination of proteomic and transcriptomic approaches, we examined whether there is a direct correlation between the functional similarity of regions and the similarity of their associated toxin expression profiles. We report that the regionalization of toxin production is consistent with the partitioning of the ecological roles of venom across envenomating structures, and that three major functional regions are present in T . stephensoni : tentacles, epidermis and gastrodermis. Additionally, we find that most structures that serve similar functions not only have comparable putative toxin profiles but also similar nematocyst types. There was no overlap in the putative toxins identified using proteomics and transcriptomics, but the expression patterns of specific milked venom peptides were conserved across RNA‐sequencing and mass spectrometry imaging data sets. Furthermore, based on our data, it appears that acontia of T . stephensoni may be transcriptionally inactive and only mature nematocysts are present in the distal portions of the threads. Overall, we find that the venom profile of different anatomical regions in sea anemones varies according to its ecological functions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

A process of convergent amplification and tissue‐specific expression dominates the evolution of toxin and toxin‐like genes in sea anemones - Joachim M. Surm; Hayden L. Smith; Bruno Madio; Eivind A.B. Undheim; Glenn F. King; Brett R. Hamilton; Chloé A. van der Burg; Ana Pavasovic; Peter J. Prentis (Molecular Ecology, 2019)
Members of phylum Cnidaria are an ancient group of venomous animals and rely on a number of specialized tissues to produce toxins in order to fulfil a range of ecological roles including prey capture, defence against predators, digestion and aggressive encounters. However, limited comprehensive analyses of the evolution and expression of toxin genes currently exist for cnidarian species. In this study, we use genomic and transcriptomic sequencing data to examine gene copy number variation and selective pressure on toxin gene families in phylum Cnidaria. Additionally, we use quantitative RNA‐seq and mass spectrometry imaging to understand expression patterns and tissue localization of toxin production in sea anemones. Using genomic data, we demonstrate that the first large‐scale expansion and diversification of known toxin genes occurs in phylum Cnidaria, a process we also observe in other venomous lineages, which we refer to as convergent amplification. Our analyses of selective pressure on sea anemone toxin gene families reveal that purifying selection is the dominant mode of evolution for these genes and that phylogenetic inertia is an important determinant of toxin gene complement in this group. The gene expression and tissue localization data revealed that specific genes and proteins from toxin gene families show strong patterns of tissue and developmental‐phase specificity in sea anemones. Overall, convergent amplification and phylogenetic inertia have strongly influenced the distribution and evolution of the toxin complement observed in sea anemones, while the production of venoms with different compositions across tissues is related to the functional and ecological roles undertaken by each tissue type.

The world’s largest parrotfish has slow growth and a complex reproductive ecology - Brett M. Taylor; Richard J. Hamilton; Glenn R. Almany; J. Howard Choat (Coral Reefs, 2018)

Urban particulate matter activates Akt in human lung cells - Todd L. Watterson; Brett Hamilton; Randy S. Martin; Roger A. Coulombe (Archives of Toxicology, 2012)

Simulation of vertical position of buoyancy regulating Microcystis aeruginosa in a shallow eutrophic lake - Brett B. Wallace; Mark C. Bailey; David P. Hamilton (Aquatic Sciences, 2000)

The effect of variations in irradiance on buoyancy regulation in Microcystis aeruginosa - Brett B. Wallace; David P. Hamilton (Limnology and Oceanography, 1999)
A mechanism of buoyancy regulation in cyanobacteria was investigated in a fluctuating light environment typical of the mixed layer in a lake. New measurements of density and cellular carbohydrate content were obtained from a field sample of the cyanobacterium Microcystis aeruginosa . The rate of increase in carbohydrate and density in this cyanobacterium does not instantaneously adjust to an increase in light intensity. There is a time lag, the response time, corresponding to physiological adjustment to the increase in light, before equilibration of the rate of carbohydrate and density increase. Also, the rate of density and carbohydrate increase is nonlinear over the response time. Based on these experimental findings, a new model for buoyancy regulation was developed that includes the response time. This model was applied to two fluctuating light regimes that simulate Langmuir circulation and turbulence. The simulations reveal that the response time is critical in determining if a cell equilibrates its rate of density change to a change in the light that it receives. If the response time is longer than the time scale of the light fluctuation, then the rate of density increase will be less than the optimal equilibrium rate. Models that do not include the response time will not correctly predict the buoyancy of cyanobacteria and their water column position after an episode of mixing.